Detection and isolation of circulating tumor cells from breast cancer patients using CUB domain-containing protein 1 - Bartkowiak, Kai; Mossahebi Mohammadi, Parinaz; Gärtner, Sebastian; Kwiatkowski, Marcel; Andreas, Antje; Geffken, Maria; Peine, Sven; Verpoort, Karl; Scholz, Ursula; Deutsch, Thomas M.; Michel, Laura L.; Schneeweiss, Andreas; et al. (Journal of proteome research, 2023)
In cancer metastasis, single circulating tumor cells (CTCs) in the blood and disseminated tumor cells (DTCs) in the bone marrow mediate cancer metastasis. Because suitable biomarker proteins are lacking, CTCs and DTCs with mesenchymal attributes are difficult to isolate from the bulk of normal blood cells. To establish a procedure allowing the isolation of such cells, we analyzed the cell line BC-M1 established from DTCs in the bone marrow of a breast cancer patient by stable isotope labeling by amino acids in cell culture (SILAC) and mass spectrometry. We found high levels of the transmembrane protein CUB domain-containing protein 1 (CDCP1) in breast cancer cell lines with mesenchymal attributes. Peripheral blood mononuclear cells were virtually negative for CDCP1. Confirmation in vivo by CellSearch revealed CDCP1-positive CTCs in 8 of 30 analyzed breast cancer patients. Only EpCam-positive CTCs were enriched by CellSearch. Using the extracellular domain of CDCP1, we established a magnetic-activated cell sorting (MACS) approach enabling also the enrichment of EpCam-negative CTCs. Thus, our approach is particularly suited for the isolation of mesenchymal CTCs with downregulated epithelial cancer that occur, for example, in triple-negative breast cancer patients who are prone to therapy failure.